2019
DOI: 10.1212/nxi.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Trial of canakinumab, an IL-1β receptor antagonist, in patients with inclusion body myositis

Abstract: ObjectiveTo assess whether canakinumab, a monoclonal antibody against IL-1β approved for autoinflammatory diseases, is effective as target-specific therapy in patients with sporadic inclusion body myositis (sIBM).MethodsBecause in sIBM IL-1β colocalizes with amyloid precursor protein and upregulates amyloid aggregates enhancing degeneration, targeting IL-1β with canakinumab may arrest disease progression. On this basis, 5 ambulatory patients with sIBM participated in an institutional review board--approved ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…The active involvement of IL-1 in the inflammatory process leads to the development of targeted therapies using IL-1 blockade. Yet the clinical results of IL-1β blockade were mixed [ 38 40 ]. Zong et al [ 38 ] reported a satisfactory outcome of anakinra treatment in patients with refractory inflammatory myopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active involvement of IL-1 in the inflammatory process leads to the development of targeted therapies using IL-1 blockade. Yet the clinical results of IL-1β blockade were mixed [ 38 40 ]. Zong et al [ 38 ] reported a satisfactory outcome of anakinra treatment in patients with refractory inflammatory myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, 3 out of 6 PM patients, 3 out of 4 dermatomyositis (DM), and 1 out of 5 inclusion body myositis (IBM), showed clinical response to anakinra treatment. However, other reports using IL-1β blockade (canakinumab or anakinra) to treat IBM showed less satisfactory results [ 39 , 40 ]. Further understanding of the molecular mechanisms of IL-1β in the pathogenesis of myositis is required.…”
Section: Discussionmentioning
confidence: 99%
“…The active involvement of IL-1 in the in ammatory process leads to the development of targeted therapies using IL-1 blockade. Yet the clinical results of IL-1β blockade were mixed [38][39][40]. Zong et al [38] reported a satisfactory outcome of anakinra treatment in patients with refractory in ammatory myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids, methotrexate, cyclosporine, azathioprine, or mycophenolate is ineffective, and although some patients initially experience mild improvements, there is no long-term benefit. Treatment with alemtuzumab, a B and T cell-depleting anti-CD52 monoclonal antibody, has shown some promising results in an uncontrolled trial [ 25 ], while treatment with canakinumab, an anti-IL-1β monoclonal antibody, yielded mixed results in a small trial of 5 patients [ 26 ]. Anakinra, an IL-1 receptor blocker, had also shown mild short-term improvements in a subset of patients in the first series [ 27 ] and in a later study of 15 patients [ 28 ].…”
Section: Autoimmune Neurological Disorders With Dysphagiamentioning
confidence: 99%